2012
DOI: 10.1007/s12275-012-1573-z
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of the efficacy of a pre-pandemic H5N1 vaccine (MG1109) in mouse and ferret models

Abstract: The threat of a highly pathogenic avian influenza (HPAI) H5N1 virus causing the next pandemic remains a major concern. In this study, we evaluated the immunogenicity and efficacy of an inactivated whole-virus H5N1 pre-pandemic vaccine (MG1109) formulated by Green Cross Co., Ltd containing the hemagglutinin (HA) and neuraminidase (NA) genes of the clade 1 A/Vietnam/1194/04 virus in the backbone of A/Puerto Rico/8/34 (RgVietNam/04xPR8/34). Administration of the MG1109 vaccine (2-doses) in mice and ferrets elicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Dose-sparing strategies have been previously studied for seasonal influenza [3133] and, more recently, for pandemic scenarios [11,12, 3545]. Previous work suggests that, in a pandemic, an antigen-sparing strategy, where only a single dose of vaccine is given instead of two, is optimal to minimize illness attack rates for primary response levels in the vicinity of 0.50 [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dose-sparing strategies have been previously studied for seasonal influenza [3133] and, more recently, for pandemic scenarios [11,12, 3545]. Previous work suggests that, in a pandemic, an antigen-sparing strategy, where only a single dose of vaccine is given instead of two, is optimal to minimize illness attack rates for primary response levels in the vicinity of 0.50 [13].…”
Section: Discussionmentioning
confidence: 99%
“…However, the efficacy of H5N1 vaccines in humans remains unproven [9]. Animal challenge studies suggest these vaccines are protective [1012], but extrapolating these results to efficacy in humans remains poorly understood. Generally two doses of vaccine are recommended to achieve full efficacy for an individual.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, universal vaccines designed to be more broadly reactive to various influenza strains and vaccines immunogenic to the specific emerging viruses are being developed [ 101 ]. Although the major purpose of mouse-adaptation studies with avian influenza were to investigate the molecular determinants altering virulence of avian virus in mammalian hosts, abundant studies have demonstrated the protective efficacy of various intervention approaches using the lethal mouse-adapted avian influenza viruses in mouse model [ 102 103 104 105 106 107 ]. Since a mouse-adapted H5N2 virus was originated from LPAI H5N2 [ 28 ] and exhibited high lethality in mice, it can therefore be used in BL-2 facility which makes it accessible and usable by more researchers interested in evaluating the efficacy of newly developing vaccines.…”
Section: Evaluation Of Protective Efficacy Of Vaccines and Therapeutimentioning
confidence: 99%
“…Studies have shown that inactivated whole H5N1 virus given as a pre-exposure vaccine can protect mice from homologous and heterologous challenge with HPAI H5N1 viruses 10 11 12 , and can protect against challenge in other animal models including ferrets 13 14 15 and non-human primates 16 . In contrast, post-exposure vaccines against HPAI H5 viruses have not been investigated, even though post-exposure vaccines against other viruses such as rabies, hepatitis B, and smallpox have worked successfully 17 18 19 .…”
mentioning
confidence: 99%